1993
DOI: 10.1007/bf01531914
|View full text |Cite
|
Sign up to set email alerts
|

Firm-size distribution and price-cost margins in Dutch manufacturing

Abstract: ABSTRACT. Industrial economists surmise a relation between the size distribution of firms and performance. Usually, attention is focused on the high end of the size distribution. The widely used four-firm seller concentration ratio, C4, ignores what happens at the low end of the size distribution.We investigate to what extent the level and the growth of small business presence influence price-cost margins in Dutch manufacturing. We use a large data set of 66 industries for a thirteen year period. This allows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The two-equation model (1) is estimated using nonlinear 3SLS with adjustment for first-order autocorrelation and heteroscedasticity: see Prince and Thurik (1993) for details of a similar adjustment procedure. The results are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The two-equation model (1) is estimated using nonlinear 3SLS with adjustment for first-order autocorrelation and heteroscedasticity: see Prince and Thurik (1993) for details of a similar adjustment procedure. The results are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…By setting the price above the competitive level, profitability increases. Consequently, more capital-intensive industries may have a higher level of price-cost margins in comparison to less capital-intensive industries (Strickland & Weiss, 1976;Domowitz, Hubbard, & Petersen, 1986a;Prince & Thurik, 1993;Go, Kamerschen, & Delorme, 1999, Goldar & Aggarwal, 2005. However, at the mature phase of the industry, due to excess capacity capital investments could negatively affect profitability (Lieberman, 1987;Dickinson & Sommers, 2012).…”
Section: Capital Intensitymentioning
confidence: 99%
“…Firms with a higher capital investment in an intensive market can have higher profitability in considerate of newer competitors (Prince & Thurik, 1992). In several earliest studies, Strickland and Weiss (1976); Domowitz, Hubbard, and Petersen (1986); Prince and Thurik (1993) it is argued that compared with less capital-intensive industries, highly capital-intensive industries earn a higher margin which result in higher profitability. However, in a recent study, Dickinson and Sommers (2012) found that excess capital investment in the mature phase of a company can negatively influence the profitability.…”
Section: Capital Intensitymentioning
confidence: 99%